2021
DOI: 10.1053/j.ajkd.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Burden of the COVID-19 Pandemic for People With Kidney Disease

Abstract: H ealth authorities worldwide began to recognize the enormity of the coronavirus disease 2019 pandemic late in the first quarter of 2020. The daunting public health implications of the pandemic for people with kidney disease has since become increasingly clear. Indeed, reports on the impact of COVID-19 in people with kidney disease have appeared at a rate unprecedented in the history of nephrology.In this issue of AJKD, the report by Chung et al 1 provides important insights into 2 questions of supreme import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…7,8,11,29 A potential confounder to these relationships is that older patients with more comorbidities may be more likely to get tested because of more symptomatic illness or more frequent hospitalization. 5,6 We found that non-White ethnicity, lower income, and residency in long-term care homes were associated with a higher risk of infection, as has been previously reported in the maintenance dialysis population. 1 This emphasizes the importance of socioeconomic factors in COVID-19 infection.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…7,8,11,29 A potential confounder to these relationships is that older patients with more comorbidities may be more likely to get tested because of more symptomatic illness or more frequent hospitalization. 5,6 We found that non-White ethnicity, lower income, and residency in long-term care homes were associated with a higher risk of infection, as has been previously reported in the maintenance dialysis population. 1 This emphasizes the importance of socioeconomic factors in COVID-19 infection.…”
Section: Discussionsupporting
confidence: 80%
“…CKD is a strong risk factor for severe coronavirus disease 2019 (COVID-19)–related outcomes including hospitalization and all-cause mortality. 110 People on maintenance dialysis and with kidney transplants were identified early in the pandemic as subgroups at higher risk for severe outcomes and were prioritized in global vaccination efforts. 11,12…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study's author provides similar statistics, stating that the mortality rate in such patients increases by 20-30%. J.B. Wetmore [22] presented information that about 4.0% of patients on renal replacement therapy who are hospitalised for a cardiovascular event die in the hospital and another 4.5% of discharged patients die within the next 30 days. It has also been proven that not all patients with COVID-19 can be hospitalised and, therefore, are not included in trials, so the mortality rate is likely to be even higher.…”
Section: Discussionmentioning
confidence: 99%